Global Economic Prospects, June 2014 : Shifting Priorities, Building for the Future - World Bank (Washington, DC, 2014)
The global economy got off to a bumpy start this year, but growth in 2015 and 2016 looks to be broadly on track. Projections for developing countries in 2014 have been down downgraded by 0.5 percentage points to 4.8 percent mainly reflecting weak first quarter growth in the US due to weather and the conflict in Ukraine. Going forward growth is projected to firm to 5.3 and 5.5 percent in 2015 and 2016 supported by easy global financial conditions and rebounding exports as high-income countries continue to recover under the influence of a reduced drag from fiscal consolidation and improving labor markets. Financial conditions will eventually tighten, and when they do there is risk of further volatility. Most developing countries are in good fiscal and financial shape, but where vulnerabilities remain countries need to tighten policy to reduce the potential impact of external shocks. Overall, growth for developing countries will be solid but not strong enough to generate the income and employment gains needed to eliminate poverty by 2013. As a result, countries need to focus on structural reform in order to lift growth in and enduring and sustainable manner.